2011
DOI: 10.1007/s11325-011-0520-2
|View full text |Cite
|
Sign up to set email alerts
|

Catathrenia under sodium oxybate in narcolepsy with cataplexy

Abstract: Catathrenia should be considered a possible side effect in NC patients under SO treatment and should be accurately identified to prevent unnecessary SO withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…While sodium oxybate can improve excessive daytime sleepiness and cataplexy, it is also known to be a respiratory depressant at higher doses, raising concern that it could worsen sleep apnea. Though current data is mixed regarding this possibility, [992][993][994][995] the use of sodium oxybate in a patient with narcolepsy could potentially contribute to the development or worsening of OSA and repeat screening for this may pursued in certain clinical contexts.…”
Section: Viii3 Narcolepsymentioning
confidence: 99%
“…While sodium oxybate can improve excessive daytime sleepiness and cataplexy, it is also known to be a respiratory depressant at higher doses, raising concern that it could worsen sleep apnea. Though current data is mixed regarding this possibility, [992][993][994][995] the use of sodium oxybate in a patient with narcolepsy could potentially contribute to the development or worsening of OSA and repeat screening for this may pursued in certain clinical contexts.…”
Section: Viii3 Narcolepsymentioning
confidence: 99%
“…These complaints are usually brought up by their bed partners as it disrupts their quality of sleep. Recent studies have also reported episodes of catathrenia secondary to sodium oxybate in the management of patients with narcolepsy [34]. Continuous positive airway pressure (CPAP) is found to be effective in the management of catathrenia.…”
Section: Reviewmentioning
confidence: 99%
“…Şimdiye kadar, katatreni ile ilgili herhangi bir predispozan faktör veya net etiyoloji gösterilmemiştir. Katatreni ile bruksizm, yüzme aktivitesi ve sodyum oksibat kullanımı arasında ilişki olduğu bildirilmiştir (4,8,13). Olgumuzda bu faktörlerden hiçbirisi yoktur.…”
Section: Discussionunclassified